Analysis Study of the Relationship Between Tahsinul Qur'an with Maharah Qira'ah | Kajian Analisis Hubungan Antara Tahsinul Qur’an Dengan Maharah Qira’ah - Nisa, Kurniaan Lailatun; Izzah, Nailul; Putri, Wakhidatul Nurrohmah (NAJAH BESTARI, 2025)
Tahsinul Qur'an is the skill of reading the Qur'an correctly according to the law of tajweed, while maharah qira'ah is the ability to read and understand Arabic texts. Both have similarities in reading texts that are both in Arabic. This study aims to analyze the relationship between tahsinul qur'an and maharah qira'ah in female students of the book class of the Ma'arif Nahdhotul Ulama Metro Islamic Boarding School, Lampung. The focus of this study is motivated by the imbalance of ability between the reading of the Qur'an tartly and the ability to read and understand general Arabic texts. This study uses a quantitative approach with an associative correlation method. Data was obtained through tests, observations, and documentation, and analyzed using SPSS version 25 software. The research sample amounted to 39 students who were selected using the stratified random sampling technique. The results showed a correlation value of 0.159 with a significance of 0.334 > 0.05, which means that there is no significant relationship between the tahsinul of the Qur'an and maharah qira'ah. This is due to the difference in focus between the two; The tahsinul of the Qur'an emphasizes the phonetic and tajweed aspects, while the maharah qira'ah focuses on the rules of nahwu, shorof, and understanding of meaning.